2011
DOI: 10.1016/j.jvs.2010.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Sex, race, and age distributions of mean aortic wall thickness in a multiethnic population-based sample

Abstract: Age, gender, and racial/ethnic differences in MAWT distributions exist in the general population. Such differences should be considered in future investigations assessing aortic atherosclerosis and the effects of anti-atherosclerotic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…We observed that the association between aging and cf‐PWV cannot be explained by classic risk factors in brown and mainly in black women in the highest cf‐PWV quartile. Additionally, our results are in agreement with a study that included participants in the Dallas Heart Study30 who had a magnetic resonance imaging of the abdominal aorta that did not detect differences in aortic thickness among ethnic groups in men. However, black women had greater wall thickness than white or Hispanic women 30.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the association between aging and cf‐PWV cannot be explained by classic risk factors in brown and mainly in black women in the highest cf‐PWV quartile. Additionally, our results are in agreement with a study that included participants in the Dallas Heart Study30 who had a magnetic resonance imaging of the abdominal aorta that did not detect differences in aortic thickness among ethnic groups in men. However, black women had greater wall thickness than white or Hispanic women 30.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, our results are in agreement with a study that included participants in the Dallas Heart Study30 who had a magnetic resonance imaging of the abdominal aorta that did not detect differences in aortic thickness among ethnic groups in men. However, black women had greater wall thickness than white or Hispanic women 30. These differences might be explained by other factors, such as genetic background, novel cardiovascular risk factors, or socioeconomic/psychosocial factors.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we extend to small arteries the previous demonstration that in large arteries, such as the aorta [28] or the carotid [29], ageing and hypertension had trophic effects on arterial wall. Concerning arterioles, previous imaging methods had already detected enlargement with age [30].…”
Section: Discussionmentioning
confidence: 61%
“…3 There are reports of age-related increases of arterial wall thickness (AWT) in several cross-sectional community-based studies; 4,5 however, rates of change in AWT among middle-aged and older adults have not been defined. Moreover, the relationship between AWT and aortic stiffness after accounting for cardiovascular risk factors has not been defined.…”
Section: Introductionmentioning
confidence: 99%